Dampak Human Capital, Structural Capital, Dan Costumer Capital Terhadap Kinerja Bisnis UMKM Di Tilamuta - Hasmirati Hasmirati; Alfin Akuba (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2022)
AbstractThis study aims to determine and analyze how much impact human capital, structural capital, and customer capital have on the business performance of MSME workshops in Tilamuta sub-district. This research is quantitative research. The method of analysis using multiple linear regression. The results of the study show that, human capital, structural capital and customer capital simultaneously have a significant effect on the performance of the UMKM workshop business. Human capital partially has a significant effect on the business performance of MSME workshops because they have knowledge, expertise, and abilities. Structural capital partially has a significant effect on the business performance of MSME workshops including organizational culture, organizational structure, organizational learning, organizational processes and organizational systems. Partially, customer capital has a significant effect on MSME business performance. Bengel covers brand value, customer network, customer loyalty and customer satisfaction. Keywords: Human Capital, Structural Capital, Customer Capital and MSME Performance